Soil organic carbon and root biomass of Quercus sp. - Gómez, Jesús D.; Etchevers, Jorge D.; Monterroso, Alejandro I.; Campo, Julio; Paustian, Keith; Asensio, Carlos (Instituto de Ecología, A.C., 2021)
The distribution of the biomass of fine, medium, and thick roots, the concentration of soil organic carbon (COS), the apparent density (Da), the COS stores in the first 90 cm of depth were studied in three forests with a predominance of oak (Quercus sp.) located in central Mexico (Morelos) The estimated age of the trees in the forests was (a) ≈ 40 years or late, (b) ≈ 20 years, and (c) ≈ 10 years or earlier. We found that the SOC concentration and SOC stores decreased as the soil depth increased while the Da increased. More than half of the stored COS accumulates in the first 30 cm of the profile. The biomass of fine roots presented an exponential decrease pattern as depth increased, while the biomass of medium and thick roots had an irregular pattern, but always with a tendency to decrease as depth did. In the forests of the three indicated ages, the biomass of fine, medium, and thick roots had a higher correlation with Da than with COS stores. The regression coefficients (R2) of the linear models relating Da to the COS content were in the range of 0.61 and 0.72.